Web-Based Swine Disease Diagnosis Expert System Using Forward Chaining in Waingapu City District - Ndamu, Tomi Umbu; Pingky Alfa Ray Leo Lede, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The policy of the East Sumba Regency Livestock Office is to advance the business of livestock products and in developing an information system about the distribution of livestock populations in East Sumba Regency in an integrated and comprehensive manner to the community and make it easier for the community to find out the development of the number of livestock populations in East Sumba Regency. Pigs are a type of ungulated animal with a long snout and a straight nose and are animals that originally originated in Eurasia. Also known as Pig in (Arabic). Pigs are omnivores, which means they eat both meat and plants. However, with the large existing pig population, consumption and population resulting in the potential for much higher disease, let alone infectious diseases. The problem found in pig farmers is that it is difficult for farmers to identify the type of disease by pigs. Misdiagnosis gives rise to errors in treatment or errors in treating sick pigs. Therefore, based on these problems, the author proposes a system-based approach to assist farmers in diagnosing the types of diseases experienced by pigs. So that the treatment of pigs can be more targeted according to the disease diagnosed.